1999
DOI: 10.1002/jlb.65.6.744
|View full text |Cite
|
Sign up to set email alerts
|

Differential production of MCP-1 and cytokine-induced neutrophil chemoattractant in the ischemic brain after transient focal ischemia in rats

Abstract: Chemokines have been shown to play an important role in leukocyte infiltration into ischemic lesions. Recently, the increased expression of monocyte chemoattractant protein-1 (MCP-1) and cytokine-induced neutrophil chemoattractant (CINC) was observed in experimental stroke models where infiltrated leukocytes were supposed to induce tissue injury, however, the protein level and time course of these chemokines have not been fully elucidated. Therefore, we analyzed the timedependent production of MCP-1 and CINC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(80 citation statements)
references
References 41 publications
1
75
2
Order By: Relevance
“…Enhanced expression of mRNAs for monocyte chemoattractant protein-1 (MCP-1, CCL2) (26 -28), and macrophage inflammatory protein-1α (MIP-1α, CCL3) (26,29) was demonstrated in the ischemic brain using a rat MCAO model. Increase in the peptide contents of MCP-1 / CCL2 has been also shown in the brain after the ischemic insult (30). Cell species expressing these chemokine mRNAs were examined by a double in situ hybridization technique (28,29).…”
Section: Enhanced Production and Release Of Chemokines In The Ischemimentioning
confidence: 99%
“…Enhanced expression of mRNAs for monocyte chemoattractant protein-1 (MCP-1, CCL2) (26 -28), and macrophage inflammatory protein-1α (MIP-1α, CCL3) (26,29) was demonstrated in the ischemic brain using a rat MCAO model. Increase in the peptide contents of MCP-1 / CCL2 has been also shown in the brain after the ischemic insult (30). Cell species expressing these chemokine mRNAs were examined by a double in situ hybridization technique (28,29).…”
Section: Enhanced Production and Release Of Chemokines In The Ischemimentioning
confidence: 99%
“…After ischemia, messenger RNA expression of potent inflammatory cytokines and chemokines TNF-a, IL-1b, and MCP-1 increases in the brain within 1 to 3 hours and peaks between 24 and 36 hours. [4][5][6][7][8][9][10] Increases in protein levels of these factors occur by 6 hours after stroke (ref. 4 and our data) in neurons, glia, peripheral immune organs, and circulating immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the levels of proinflammatory cytokines such as tumor necrosis factor-α and interleukin-1β, chemokines such as monocyte chemoattractant protein-1 (MCP-1), and macrophage inflammatory protein-1α are markedly increased in the brain after middle cerebral artery occlusion (3 -6). Cytokine-induced neutrophil chemoattractant-1 (CINC-1), a member of the CXC chemokine family, is also upregulated in the ischemic brain (5,7,8). Under ischemic conditions, leukocytes infiltrate into the brain parenchyma from the circulation.…”
Section: Introductionmentioning
confidence: 99%